2004
DOI: 10.1653/0015-4040(2004)087[0037:nbozah]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Biology of Zeta Argillaceum (Hymenoptera: Vespidae: Eumeninae) in Southern Florida, U.S.

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Previous records indicated that other species of the genus nest on plant stems (Pérez D'Angello 1974, 1991. There are species of Eumeninae which attach their nests to human-built structures (Camillo 1999;Matthews & González 2004;Matthews & Matthews 2009). The utilization of this type of substrate becomes important for the establishment and nidification of potter wasps in areas of high human intervention, providing potential habitats for them.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous records indicated that other species of the genus nest on plant stems (Pérez D'Angello 1974, 1991. There are species of Eumeninae which attach their nests to human-built structures (Camillo 1999;Matthews & González 2004;Matthews & Matthews 2009). The utilization of this type of substrate becomes important for the establishment and nidification of potter wasps in areas of high human intervention, providing potential habitats for them.…”
Section: Resultsmentioning
confidence: 99%
“…Building this funnel-like structure around the entrance orifice of the cell plays an important role in the protection of the cell during the prey filling process carried out by the female (Matthews & Matthews 2009). This funnel-like structure can be relatively small sized when compared to the cell's size, such as in the case of H. andeus and Zeta argillaceum (Linnaeus, 1758) (Matthews & González 2004). In some cases this structure can reach sizes even larger than the cell itself, as in the Australian species A. ephippium (Matthews & Matthews 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On one hand, their most commonly acknowledged function is herbivory, because their abundance levels may be high among the external chewers of some plants (Bodner et al 2012). On the other hand, they may be also extremely important as prey for insectivorous organisms (Matthews & González 2004;Marconato et al 2008).…”
mentioning
confidence: 99%